Plant-Derived Exosomes: Nano-Inducers of Cross-Kingdom Regulations - Touseef Ur Rehman; Huiliang Li; Maria Martuscelli; Francesca Aiello; Luigi Esposito; Kamran Ashraf; Meijin Guo; Ali Mohsin (Pharmaceuticals)
Exosomes are essential components produced by all cell types, originating from the endosomal pathway through the invagination of the cell membrane. Their unique physicochemical characteristics are crucial for various commercial applications. Typically, exosomes range in size from 50 to 200 nm. Exosomes derived from plant cells are larger than their animal cell counterparts and demonstrate a broader therapeutic potential. This review explores the promising research opportunities associated with plant-derived exosomes, summarizing studies on their biogenesis, characterization, isolation methods, and therapeutic applications. It also emphasizes the importance of targeted drug delivery and provides insights into engineering plant-derived exosomes with various drugs. Additionally, highlights of plant-derived exosomes as natural nano-inducers that facilitate inter-kingdom communication and cross-kingdom regulatory interactions are also elucidated herein. Henceforth, this study culminates in a multidimensional insight for innovative therapeutic strategies and biotechnological advancements in plant-derived exosome research.